Additive antinociceptive effects of mixtures of the κ-opioid receptor agonist spiradoline and the cannabinoid receptor agonist CP55940 in rats. Issue 1 (February 2016) - Maguire, David R.; France, Charles P.
Abstract : Pain is a significant clinical problem, and there is a need for pharmacotherapies that are more effective with fewer adverse effects than currently available medications. Cannabinoid receptor agonists enhance the antinociceptive effects of μ-opioid receptor agonists; it is unclear whether they impact the effects of agonists acting at other opioid receptors. κ-Opioid receptor agonists have antinociceptive effects, but their clinical use is precluded by adverse effects; however, their therapeutic potential might be realized if antinociceptive effects could be selectively enhanced. In this study, the antinociceptive effects of the cannabinoid receptor agonist CP55940 and the κ-opioid receptor agonist spiradoline, alone and in combination, were studied in rats ( n =7) using a warm water tail-withdrawal procedure. When administered alone, CP55940 (0.032–1.0 mg/kg) and spiradoline (1.0–32.0 mg/kg) increased tail-withdrawal latency, and mixtures of CP55940 and spiradoline (ratios of 1 : 3, 1 : 1, and 3 : 1) produced additive effects. It remains to be determined whether this additive interaction between a κ-opioid receptor agonist and a cannabinoid receptor agonist is selective for antinociception and whether it can be generalized to other drugs.